Gender Disparity and the Association Between Socioeconomic Status, Mental Health, and the Need for Long-Term Services and Support Among the Older Koreans - Zhao, Bo; Kong, Fanlei; Shin, Dong Eun; Nam, Eun Woo (Frontiers in Public Health, 2022)
Background Population aging—the inevitable increase in the percentage of older adults—is occurring all around the world as the fertility rate declines and life expectancy rises. This study examined the relationship between socioeconomic status (SES), mental health, and the need for long-term services and support (LTSS) among Korean older adults. It also aimed to provide evidence-based information for South Korea's long-term support services and programs. Methods This study used the data on older adults aged over 60 years from the 2018 Korean Longitudinal Study of Aging (KLoSA). Ultimately, 5,527 older adults were included in the database (42.6% men, 57.4% women). To clarify the association between SES, mental health, and the need for LTSS among older Korean men and women, chi-squared test, t-test, and structural equation modeling (SEM) were performed. Results The SEM analysis showed that a significant, negative association was observed between SES and the need for LTSS among these older adults—the higher SES groups would generally have less need for LTSS. Mental health had a strong, negative impact on the need for LTSS—better mental health status of the older individuals would indicate a lower need for LTSS, and the effect was stronger among older men. Meanwhile, the positive relationship between SES and mental health was verified—the higher the SES of these older adults the better their mental health. Conclusions Gender- and social class-sensitive impacts of mental health on the need for LTSS were observed in this study. These findings could provide an evidence-based reference for interventions targeting different genders and social classes in Korea's long-term care system, such as the enhancement of social welfare and mental health status of the older adults.